.1(.1x+.9)=

Simple and best practice solution for .1(.1x+.9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .1(.1x+.9)= equation:


Simplifying
0.1(0.1x + 0.9) = 0

Reorder the terms:
0.1(0.9 + 0.1x) = 0
(0.9 * 0.1 + 0.1x * 0.1) = 0
(0.09 + 0.01x) = 0

Solving
0.09 + 0.01x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.09' to each side of the equation.
0.09 + -0.09 + 0.01x = 0 + -0.09

Combine like terms: 0.09 + -0.09 = 0.00
0.00 + 0.01x = 0 + -0.09
0.01x = 0 + -0.09

Combine like terms: 0 + -0.09 = -0.09
0.01x = -0.09

Divide each side by '0.01'.
x = -9

Simplifying
x = -9

See similar equations:

| 3y=3y+18 | | -6(x-2)=12-3x | | 15+6x=25+5x | | 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 | | -6.47-10.16= | | 4x^2+3=-18x | | +0-(+12)= | | ((5)/(2x+4)+4)=((-1)/(x+2)) | | 1=x+23 |

Equations solver categories